Party competition and citizens' political attitudes in the American states. (December 2016) - Flavin, Patrick; Shufeldt, Gregory
Abstract: Democratic theorists argue that vigorous competition between candidates/parties is essential for democracy to flourish because it engages citizens' political interest and ultimately makes elected officials more accountable to their constituents. Using data on citizens' perceptions of government responsiveness to their political opinions from the American National Election Studies and the Ranney measure of party competition for control of state government, we examine the effects of competition on citizens' political attitudes from 1952 to 2008. Our analysis reveals that citizens feel government is more responsive to them when there is greater competition between the two parties for control of government in their state. However, this relationship is confined only to citizens who identify with the party that controls government in their state. We also find that the relationship between competition and efficacy is strongest among citizens with lower levels of education and income. These results suggest that vigorous competition for control of state government can have important implications for citizens' political attitudes. Highlights: We examine state party competition and citizens' political attitudes for 1952–2008. Citizens feel government is more responsive when there is greater party competition. Relationship confined only to citizens who identify with their state's majority party. Relationship strongest among citizens with lower levels of education and income.